Pengujian Konstitusionalitas Pasal 239 UU MD3: Dominasi Partai Politik Dan Hilangnya Kedaulatan Pemilih Dalam Mekanisme PAW - Rafif Rizqullah; Titin; Muhamad Rafi Mahardika Agustiar; Dandy Romero Firdaus (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2025)
The regulation on Interim Replacement (PAW) under Article 239 of Law Number 17 of 2014 concerning the MPR, DPR, DPD, and DPRD (the MD3 Law) places the authority to dismiss members of the House of Representatives entirely in the hands of political parties. This normative design raises serious constitutional concerns because it severs the representational mandate between voters and the representatives they elect through direct elections as mandated by Article 1 paragraph (2) and Article 22E paragraph (1) of the 1945 Constitution. When the people, as the holders of sovereignty, have no mechanism to hold their representatives accountable during their term of office, the representative function substantively transforms into a mere extension of political parties. This condition results in the erosion of constituents’ political rights to ensure the integrity, accountability, and fidelity of their representatives to their electoral mandate, as well as creating legal uncertainty regarding the position of voters as subjects of sovereignty, which is contrary to Article 28D paragraph (1) of the 1945 Constitution.